2022
DOI: 10.1590/1517-8692202228062022_0110
|View full text |Cite
|
Sign up to set email alerts
|

Training Methods in Basketball Players to Increase Their Shooting Percentage

Abstract: Introduction In the process of basketball training, players often rely solely on shooting practice to achieve their training objectives. Improving shooting success percentage under the static and variable offensive and defensive conditions have become a significant concern for coaches and basketball enthusiasts. Objective This paper analyzes training methods to improve the shooting success percentage of basketball players. Methods The shooting success percentage between two groups of basketball players is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
(9 reference statements)
0
1
0
Order By: Relevance
“…Additionally, TVT has been found to benefit lymphocytes and blood circulation, as it involves muscle fiber contraction and relaxation processes [ 14 ]. Several studies have demonstrated that TVT workouts contribute to functional improvements, particularly in the musculoskeletal systems of athletes participating in sports such as football, basketball, figure skating, and volleyball, resulting in enhanced motor skill transfer [ [13] , [14] , [15] ].The availability of a wide range of modern training methods and tools has significantly improved training processes [ 16 , 17 ], especially those that do not require expensive equipment. For example, a study showed that TRX exercise helped active women reduce their body fat percentage and improv e upper and lower body strength and endurance [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, TVT has been found to benefit lymphocytes and blood circulation, as it involves muscle fiber contraction and relaxation processes [ 14 ]. Several studies have demonstrated that TVT workouts contribute to functional improvements, particularly in the musculoskeletal systems of athletes participating in sports such as football, basketball, figure skating, and volleyball, resulting in enhanced motor skill transfer [ [13] , [14] , [15] ].The availability of a wide range of modern training methods and tools has significantly improved training processes [ 16 , 17 ], especially those that do not require expensive equipment. For example, a study showed that TRX exercise helped active women reduce their body fat percentage and improv e upper and lower body strength and endurance [ 18 ].…”
Section: Introductionmentioning
confidence: 99%